Affinity, kinetics, and thermodynamics of E-selectin binding to E-selectin ligand-1. - Wild, M; Huang, M; Schulze-Horsel, U; Van Der Merwe, P; Vestweber, D (2001)
E-selectin is an endothelial adhesion molecule, which mediates the tethering and rolling of leukocytes on vascular endothelium. It recognizes the glycoprotein E-selectin ligand-1 (ESL-1) as a major binding partner on mouse myeloid cells. Using surface plasmon resonance, we measured the kinetics and affinity of binding of monomeric E-selectin to ESL-1 isolated from mouse bone marrow cells. E-selectin bound to ESL-1 with a fast dissociation rate constant of 4.6 s(-1) and a calculated association rate constant of 7.4 x 10(4) m(-1) s(-1). We determined a dissociation constant (K(d)) of 62 microm, which resembles the affinity of L-selectin binding to glycosylation-dependent cell adhesion molecule-1. The affinity of the E-selectin-ESL-1 interaction did not change significantly when the temperature was varied from 5 degrees C to 37 degrees C, indicating that the enthalpic contribution to the binding is small at physiological temperatures, and that, in contrast to typical protein-carbohydrate interactions, binding is driven primarily by favorable entropic changes. Interestingly, surface plasmon resonance experiments with recombinant ESL-1 from alpha 1,3-fucosyltransferase IV-expressing Chinese hamster ovary cells showed a very similar K(d) of 66 microm, suggesting that this fucosyltransferase is sufficient to produce fully functional recombinant ESL-1. Following the recent description of the affinity and kinetics of the selectin-ligand pairs L-selectin-glycosylation-dependent cell adhesion molecule-1 and P-selectin-P-selectin glycoprotein ligand-1, this is the first determination of the parameters of E-selectin binding to one of its naturally occurring ligands.